An empirical study of unbundling regulation on broadband adoption in OECD countries: What can we learn for future regulation? - Chatchai Kongaut; Erik Bohlin (International Telecommunications Society (ITS), 2012)
Broadband adoption is considered one of the drivers of both economic and social development. Local loop unbundling (LLU) regulation is one of the main strategies to open access to an incumbent's bottleneck network in order to soften its monopoly power and encourage competition in the digital subscriber line (DSL) broadband market. Many studies, however, suggest that LLU regulation can slow down new infrastructure investment. Fibre optic technology is also increasingly becoming an option for the next generation network (NGN). This development is turning out to be the new challenge for regulators, incumbents and new entrants. With the similarities to DSL broadband and the move towards technology neutrality, regulators may also be able to adjust their future next generation access (NGA) regulation by learning from the strengths and weaknesses of LLU regulation. This paper therefore aims to analyse the impacts of unbundling policy on various aspects of broadband adoption that can be presented as consumer welfare. The possible adaptation to NGA regulation is also discussed in this paper. The empirical results of this study show that LLU regulation is one of the strategies to increase broadband adoption, particularly in the countries that have difficulty encouraging infrastructure competition. Nevertheless, several studies suggest that unbundling regulation reduces the incumbent's incentive to invest. With the dramatic growth in technologies, the main policy to increase broadband penetration should be competition between them, while unbundling regulation can be implemented carefully and differently in each country that has inefficiency that is harmful to consumers in its market from a monopoly incumbent. The decision to apply access regulation from DSL to fibre technology is therefore crucial to whether the regulator regulates the NGN market from the early stage of investment or waits for the NGN market to become more mature. Alternatively, the regulator can opt not to intervene in the market for a certain period of time, as access regulation can delay the growth in infrastructure investment.
Keywords: 330; Local loop unbundling; broadband adoption; access regulation